Mouthpart Morphology, Anatomical and Histological Study of the Alimentary Canal of Coelaenomenodera lameensis (Coleoptera: Chrysomelidae), Leaf Miner of Oil Palm - Hervé, KOUA Kouakou; Mauricette, OUALI-N’GORAN San-Whouly; Marie-Anne, D’ALMEIDA; Heat, HAN Sun (Journal of Asian Scientific Research, 2011)
Coelaenomenodera lameensis Coleoptera, Chrysomelidae (Berti and Mariau, 1999) is a dangerous pest of oil palm in West Africa. In this study, we investigate for the first time, the mouthparts, the anatomy and histology of the alimentary canal of this leaf miner. Larvae mouthparts present parts size modifications from stage 1 to stage 4. Adult mouthparts are adapted for biting. The morphometric study of digestive tract showed that the midgut is the longest part whatever the stage of the insect. Histological study of the alimentary canal showed that it was divided into three main regions: stomodaeum, mesenteron and proctodaeum, both in larvae than in adult insects. Structure of these regions was particularly revealing in the foregut that the insect has anatomical structure to reduce the ingested plant.